Optimization of Social Report as a Consideration of Diversion in The Child Criminal System - Rommy Yusuf Hiola; Aliyas Aliyas; Suardi Rais (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
There is one factor that becomes an obstacle if the child has received the coaching process at the Child Special Guidance Institute (hereinafter referred to as LPKA), namely the existence of